A Green Practice on Environmental Protection: A Case of Multinational Company - Zeittey Karmilla, Kaman; Abdullah, Ibrahim; Zaleha, Othman; Andalib, Tarnima Warda (Publishing Technology, 2016)
Corporations have embraced the social responsibility rhetoric in their discourse and external reporting. However, little is known about the processes of the corporate social responsibilities practices. This paper addresses this gap by theorising the corporate social responsibilities from the aspect of environmental protection. As part of the corporate social responsibility, environmental protection has become one of the main agenda among corporations, hence this study conducted an in depth understanding by conducting a single case study at one of the Multi-National-Companies (MNC) in Malaysia. Building on Husted Conceptual Framework, this study distinguish several possible mechanism of green practices, which was identified as the core component of environmental protection. The findings indicate the green practice from the two dimension, which are structure and strategy and its association with environmental protection. Overall, this study highlights various paths towards environmental proctection from the context bound aspect of the case under study. Finally, this study support future research in terms of initiating new paradigm of corporate social responsibility in its support towards environmental proctection issues, configurating green practices framework as relevant corporate social responsibility practices.